9.09.005: "Charlie Walsh talks about confederation vote night," CD, 1985 - Walsh, Charles (1985)
Don Walsh's father Charlie remembers the night of the Newfoundland Referundum vote. He was a police officer on duty with the Newfoundland Constabulary at the time.